Antioxidative and antimicrobial properties of pulse proteins and their applications in gluten‐free foods and sports nutrition. (7th March 2022) - Shevkani, Khetan; Singh, Narpinder; Patil, Chidanand; Awasthi, Ankit; Paul, Maman
Summary: Pulses are inexpensive and eco‐friendly source of biologically active proteins/peptides exhibiting antioxidative and antimicrobial properties. The antimicrobial activity of pulse proteins/peptides is ascribed to their ability to interact with components of bacterial/fungal cells or viral‐envelope, while antioxidative effects are the result of absorption/scavenging of free radicals and reactive oxygen species, which depend on amino acid composition/sequence, hydrophobicity and molecular mass and vary with multiple factors, including, protein source, hydrolysing enzyme and conditions employed for hydrolysis. Pulse proteins also are useful for quality improvement of gluten‐free (GF) foods to fulfil the increasing demand not only of safe and nutritious but also of acceptable products for people with gluten‐related disorders. They contribute technological and sensory quality to GF baked products through providing lysine and improving hydration, viscoelasticity and gas retention, though the production of GF products with quality comparative to wheat‐based baked products is challenging. The inclusion of pulse proteins in pastas and noodles reduces their glycaemic index and improves textural and cooking properties. Also, pulse proteins were found to be comparable with animal proteins in enhancing exercise capacity and athletic performance; hence, these may be considered suitable in developing health‐promoting plant‐based athletic foods. Abstract : Properties and applications of pulse proteins.